Many thousand gone : African Americans from slavery to freedom - Hamilton, Virginia, 1936-2002.; Dillon, Leo; Dillon, Diane (New York : Knopf : Distributed by Random House, 1993)
Recounts the journey of Black slaves to freedom via the underground railroad, an extended group of people who helped fugitive slaves in many ways.
Includes bibliographical references (p.147-148) and index.
Keywords: Underground Railroad -- Juvenile literature; Fugitive slaves -- United States -- Juvenile literature; Underground Railroad; Fugitive slaves